1998
DOI: 10.1038/3068
|View full text |Cite|
|
Sign up to set email alerts
|

PML induces a novel caspase-independent death process

Abstract: PML nuclear bodies (NBs) are nuclear matrix-associated structures altered by viruses and oncogenes. We show here that PML overexpression induces rapid cell death, independent of de novo transcription and cell cycling. PML death involves cytoplasmic features of apoptosis in the absence of caspase-3 activation, and caspase inhibitors such as zVAD accelerate PML death. zVAD also accelerates interferon (IFN)-induced death, suggesting that PML contributes to IFN-induced apoptosis. The death effector BAX and the cdk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
274
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(285 citation statements)
references
References 46 publications
10
274
0
1
Order By: Relevance
“…In these cells, however, treatment with this peptide did not a ect the ability of DAPK2 to induce apoptosis (our unpublished data), suggesting that DAPK2-induced apotosis is independent of the caspase activation or DAPK2 functions downstream to the caspases. Recently, it has been reported that several types of apoptosis are not inhibited by the caspase inhibitors (Xiang et al, 1996;Miller et al, 1997;Lavoie et al, 1998;Quignon et al, 1998). DAPK2-induced cell death may contribute with these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, however, treatment with this peptide did not a ect the ability of DAPK2 to induce apoptosis (our unpublished data), suggesting that DAPK2-induced apotosis is independent of the caspase activation or DAPK2 functions downstream to the caspases. Recently, it has been reported that several types of apoptosis are not inhibited by the caspase inhibitors (Xiang et al, 1996;Miller et al, 1997;Lavoie et al, 1998;Quignon et al, 1998). DAPK2-induced cell death may contribute with these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging caspase-independent aspects of apoptosis (e.g. Quignon et al, 1998;Wang et al, 1998b) may give insights into the manner in which a death commitment signal is generated and into the exact relationship between c-Myc and mitochondrial events that are regulated by the Bcl-2 family.…”
Section: C-myc Induces Apoptosismentioning
confidence: 99%
“…PML also regulates a caspase-independent apoptosis pathway. 86 Using an inducible overexpression system, it has been shown that PML can trigger a death pathway independent from de novo protein synthesis that is not sensitive to synthetic caspase inhibitors. 86 However, this finding remains to be confirmed under more physiological conditions.…”
Section: Apoptosis Pathwaysmentioning
confidence: 99%
“…86 Using an inducible overexpression system, it has been shown that PML can trigger a death pathway independent from de novo protein synthesis that is not sensitive to synthetic caspase inhibitors. 86 However, this finding remains to be confirmed under more physiological conditions. An overview of currently known PML-NB-associated proteins and their function in cell surface receptor-mediated or nuclear apoptosis pathways are given in Table 1 and in Figure 2.…”
Section: Apoptosis Pathwaysmentioning
confidence: 99%